(untitled) (Research, Society and Development, 2022)
This study deals with the theme of knowledge, skills and competences necessary for teaching in higher education in distance education and its objective is to analyze the characteristics necessary for teaching practice for the qualification of the teaching-learning process in distance education. To achieve this objective, it contextualizes distance education, determines the knowledge, skills and competences relevant to distance teaching in higher education, where the importance of these parameters for success in the student’s education is highlighted. Through qualitative bibliographic research, it concludes that quality training must be adapted to a plural, heterogeneous, dialectical and controversial society in which knowledge, skills and competences are also in constant evolution and transformation.